2008
DOI: 10.3358/shokueishi.49.95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nitric Acid-based Partial-digestion Method for Selective Determination of Inorganic Arsenic in Rice

Abstract: Arsenic (As) uptake in human occurs via the food chain mainly. The Joint FAO/WHO Expert Committee on Food Additives has established the provisional tolerable weekly intake level for As as an inorganic As (iAs) value, because iAs in food is much more toxic than organic As. In this study, we studied an acid based partial-digestion method for the complete extraction of arsenicals from rice. HPLC/ICP-MS was used to determine the concentration of iAs selectively. The conditions adopted to extract arsenicals from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To determine As speciation in rice grain, a powdered sample of ground rice (0.5 g dry weight) was mixed with 2 mL of HNO 3 (0.15 M) in a 10 mL capped high-density polyethylene centrifuge tube, and the mixture was heated on an aluminum heating block at 80 °C for 2 h. The solution obtained was diluted to 10 mL with water and passed through a 0.45 µm filter before analysis (25). For As speciation of rice straw, ears, and stems and leaves, 5 mL of 68% aqueous HNO 3 was added to a ground powder sample (0.5 g dry weight) in a 50 mL Teflon tube, and the mixture was heated at 100 °C for 4 h. The solution obtained was diluted to 50 mL with water and passed through a 0.45 µm filter before analysis (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine As speciation in rice grain, a powdered sample of ground rice (0.5 g dry weight) was mixed with 2 mL of HNO 3 (0.15 M) in a 10 mL capped high-density polyethylene centrifuge tube, and the mixture was heated on an aluminum heating block at 80 °C for 2 h. The solution obtained was diluted to 10 mL with water and passed through a 0.45 µm filter before analysis (25). For As speciation of rice straw, ears, and stems and leaves, 5 mL of 68% aqueous HNO 3 was added to a ground powder sample (0.5 g dry weight) in a 50 mL Teflon tube, and the mixture was heated at 100 °C for 4 h. The solution obtained was diluted to 50 mL with water and passed through a 0.45 µm filter before analysis (26).…”
Section: Methodsmentioning
confidence: 99%
“…HPLC/ICP-MS analysis showed that the rice grain samples contained mostly arsenite and DMA, with trace amounts of arsenate. However, because HNO 3 is generally regarded as an oxidative acid (25), the sum of arsenite and arsenate was presented as the total inorganic As. The Student's t-test and the least-significant difference (LSD) test were used to test for statistical significance in differences between treatments.…”
Section: Methodsmentioning
confidence: 99%
“…To determine As speciation in rice grain and straw, a powdered sample of ground rice (0.5 g dry weight) was mixed with 2 mL of HNO 3 (0.15 M) in a 10 mL capped high-density polyethylene centrifuge tube, and the mixture was heated on an aluminum heating block at 80 °C for 2 h. The solution obtained was diluted to 10 mL with water and passed through a 0.45 μm filter prior to analysis. 13 As speciation in the grain, straw, soil solution and soil were determined by HPLC/ICP-MS. 14 A SuperIC-Anion column (5 μm, 4.6 mm id Â150 mm) and a guard column (Tosoh, Tokyo, Japan) with an isocratic mobile phase system consisting of 10 mM of ammonium acetate were used. The HPLC system PU 712i (GL Sciences, Tokyo, Japan) was used.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…To determine As speciation in rice grain and straw, a powdered sample of ground rice (0.5 g dry weight) was mixed with 2 mL of HNO 3 (0.15 M) in a 10 mL capped high-density polyethylene centrifuge tube, and the mixture was heated on an aluminum heating block at 80 °C for 2 h. The solution obtained was diluted to 10 mL with water and passed through a 0.45 μm filter prior to analysis …”
Section: Methodsmentioning
confidence: 99%
“…Arsenic species were extracted from the prepared rice flour samples using a heating-block extraction technique with HNO3 as the solvent. 30,31 A portion of each sample (0.5 g) was placed in a 10-mL glass tube, and 2 mL of 0.15 mol L -1 HNO3 was added. The capped tube was placed in a heating block at 100 C for 2 h. After cooling, a small volume of water was added, and the tube was centrifuged at 3500 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%